Sebaran rumpun, pola warna bulu, dan jenis tanduk domba lokal betina di Kabupaten Bandung - Ken Ratu Gharizah Alhuur; Hanif Ardhiwirayuda; An An Nurmeidiansyah; Denie Heriyadi (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
The variety of environmental and cultural conditions in each region in Indonesia causes differences in sheep rearing patterns, resulting in a variety of breeds, coat color patterns and types of horns of sheep being cultivated. The Bandung Regency area has a climate and environment that is suitable for raising livestock, so raising sheep has become a part of the culture in the area. Choosing flocks, coat color patterns and types of sheep horns that suit consumer needs can increase the selling value of sheep. The aim of this research was to determine the distribution of clump types, coat color patterns and horn types of local ewes in several animal markets in Bandung Regency. The research was conducted in June 2023 in three animal markets, namely Majalaya, Pacet, and Banjaran Animal Markets. The research method used is descriptive analytic and data collection uses the census method. Based on the research results, it can be concluded that the distribution of local ewes includes Garut sheep 86.78% and Priangan sheep 13.22%, while the distribution of local ewes's coat color patterns is dominated by white 63.64%, a combination of 25.62%, and black 10.74%, as well as muser horn types 54.55%, hornless 33.88%, and horned 11.57%. The total number of research objects was 121 animals, dominated by Garut sheep, the dominant white coat color pattern, and muser horn type